Ventriloquism and idleness in J. M. Coetzee's Life & Times of Michael K. Issue 4 (6th June 2016) - Adelman, Richard
Abstract : This essay is concerned with the resonances of idleness and repose in Coetzee's Life & Times of Michael K . It brings two contexts to bear on the novel. The first of these is the European settling of South Africa's Cape peninsula as it is described in the first essay in Coetzee's White Writing, on 'Idleness in South Africa'. The second is Samuel Taylor Coleridge's 'Eolian Harp', a poem alluded to by Coetzee in the 'Idleness' essay as well as in Youth, his second semi-fictional autobiography. The essay argues that acts of ventriloquism and what Coetzee calls 'the scandal of idleness' are central to Michael K 's politics, and that a correct consideration of these issues exposes a dark side to the novel that has not been observed by its criticism to date.